International spillovers from Euro area and US credit and demand shocks: A focus on emerging Europe. (February 2017) - Fadejeva, Ludmila; Feldkircher, Martin; Reininger, Thomas
Highlights: Euro area and US loan and aggregate demand shocks trigger significant spillovers. International effects on total credit are larger than those on output. Spillovers from US shocks have a broader global coverage than euro area shocks. Economies from emerging Europe are most vulnerable to all shocks considered. Abstract: In this paper, we examine the international effects of contractions in loan supply, loan demand and aggregate demand in the euro area and the USA. All three shocks have been at the forefront in spreading stress during the period of the global financial crisis and in particular so to countries that are strongly integrated with the euro area. We find that these shocks decrease international output and total credit to a varying degree. Loan demand and aggregate demand shocks in the euro area trigger significant negative spillovers on output in most other regions. Evidence for global negative output effects of euro area loan supply shocks is fraught with considerable estimation uncertainty. When these three types of shocks emanate from the USA, we find significant negative spillovers on output also for loan supply shocks. In general, international effects on total credit are an order of magnitude larger than those on output, with again more evidence that is significant for US than euro area shocks. Last, and taking a regional stance, our results indicate that economies from emerging Europe are most vulnerable to all shocks considered. Through their strong economic integration with the euro area, these economies are likewise exposed to euro area and US shocks, and spillover effects are often larger than the domestic response in the country of shock-origin.